ANTIDIABETIC, HYPOLIPIDEMIC AND ANTIOXIDANT ACTIVITY OF MOMORDICA CHARANTIA ON TYPE-II DIABETIC PATIENT IN ALLAHABAD INDIA. - FAROG TAYYAB; SAPNA S. LAL (International Journal of Pharma and Bio Sciences, 2013)
The present study was undertaken to investigate the antidiabetic, hypolipidemic and antioxidant effects of Momordica charantia extract on diabetic humen patients. The blood glucose level was significantly (p< 0.05) decreased in diabetic human patients after 4 and 8 weeks of treatment ascompared to diabetic control. .The administration of Momordica charantia extract on diabetic human patients for 4- 8 weeks, the total cholesterol and triglycerides levels were significantly decreased where as HDL level was increased as compared to non treated patients.. . The enzymatic antioxidants levels were decreased in diabetic control as compared to normal control. Diabetic patients treated with fruit extract of Momordica charantia for four and eight weeks the level of superoxide dismutase (8.95±0.34, 13.43±0.33 unit/mg protien) and catalase (2.28±0.14, 3.56±0.45 unit/mg protien) were increased significantly (p<0.05) as compared to diabetic control.. The non-enzymatic antioxidants such as ascorbic acid and reduced glutathione level also decrease (p<0.05) in diabetic test groups when compared to the corresponding normal control groups. The oxidative stress marker melanodialdehyde (MDA) was significant increase (p<0.05) in diabetic group as compare to the normal control group. Compared to the diabetic control there was a significant deccrease in melanodialdehyde of diabetic human patients administered fruit juice of Momordica charantia for 4week and 8 weeks. Thus, this study indicates that extract of Momordica charantia have favorable effect in hypolipidemic and hepatoprotective activities.